Smart approach for cost-effective genotyping of single nucleotide polymorphisms - Muhammad Usman Ghani; Muhammad Farooq Sabar; Muhammad Akram (Kuwait Journal of Science)
Single Nucleotide Polymorphisms (SNPs) are in prime focus of genomic studies for their probable roles in diagnostics and prognosis of diseases and forensic science. SNaPshot/minisequencing reaction based genotyping of targeted SNPs is a method of choice due to its fast and reliable detection assay. Here we described smart modifications in minisequencing reaction to make it cost effective assay for the detection of 15 SNPs in a single assay. The target SNPs were amplified in a multiplex PCR from genomic DNA and these multiplex PCR amplicons were utilized as a template in modified SNaPshot reaction for SNPs identification.  Modified protocol was assessed for reproducibility on more than 50 human DNA samples and it was observed that this modified method is at least five times more productive than original protocol recommended by the manufacturer. The current smart modifications in SNaPshot reaction were successfully optimized for asthma susceptible SNPs. However, these can be applied for cost effective genotyping of any type of genomic Single Nucleotide Polymorphisms.